2011
DOI: 10.1073/pnas.1017171108
|View full text |Cite
|
Sign up to set email alerts
|

Entropic effect on the rate of dislocation nucleation

Abstract: Dislocation nucleation is essential to our understanding of plastic deformation, ductility, and mechanical strength of crystalline materials. Molecular dynamics simulation has played an important role in uncovering the fundamental mechanisms of dislocation nucleation, but its limited timescale remains a significant challenge for studying nucleation at experimentally relevant conditions. Here we show that dislocation nucleation rates can be accurately predicted over a wide range of conditions by determining the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 39 publications
7
94
1
Order By: Relevance
“…Ryu et al 12) have shown that the entropic effect of dislocation nucleation primarily arises from thermal expansion at temperatures below 400 K. The anharmonic thermal vibration increases the equilibrium distances between each pair of atoms, and the mutual interactions become weak. It is then easier for the atomic configuration to change to a configuration that is more stable at finite temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ryu et al 12) have shown that the entropic effect of dislocation nucleation primarily arises from thermal expansion at temperatures below 400 K. The anharmonic thermal vibration increases the equilibrium distances between each pair of atoms, and the mutual interactions become weak. It is then easier for the atomic configuration to change to a configuration that is more stable at finite temperature.…”
Section: Resultsmentioning
confidence: 99%
“…This is a typical entropic effect similar to those of thermal expansion and softening. Recently, it has been shown that, for this entropic effect, the activation free energy for dislocation nucleation decreases significantly with increasing temperature, 12) which indicates that the atomic positions and motion are temperature dependent. In other words, the atomic positions and motion follow the free energy surface (FES), rather than the PES, at finite temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Adoption of an accelerated molecular dynamics scheme would be advantageous 7,8 in order to extend the range of of nucleation rates by orders of magnitude. This would allow to study the validity of the Eq.…”
Section: Discussionmentioning
confidence: 99%
“…A direct fit to this data gives a large exponential prefactor of 2.7 × 10 66 m −2 s −1 , counterbalanced by a high activation energy of 12.83 eV in the exponential function. The dramatic difference from the constant strain case is to be expected; it has already been established that the entropic contribution in a constant stress ensemble is significantly higher than the corresponding entropic contribution in the constant strain ensemble 8,9 . In Fig.…”
Section: Nucleation Rates: Dependency On Driving Force and Temperamentioning
confidence: 93%
See 1 more Smart Citation